A Tale of Transition: Trends of Catastrophic Health Expenditure and Impoverishment in Urban China, 1986-2009. Issue 1 (1st December 2020) - Song, Ze; Zhu, Yishan; Zou, Hong; Fu, Hongqiao; Yip, Winnie
ABSTRACT: From 1986 to 2009, China's health system reform first adopted a market-oriented approach and later reemphasized the role of the government starting from 2002. China's oscillating health care financing policies present us a unique opportunity to examine the consequences of government-led financing and market-oriented financing measures. This study uses the Urban Household Survey, a diary data in China that covers the period of 1986 to 2009, to examine the long-run trends in the incidence and intensity of catastrophic health expenditure and medical impoverishment. Four major findings emerge. First, the incidence and intensity of catastrophic health expenditure in urban Chinese households increased rapidly between 1986 and 2002, whereas they stabilized after 2002. Second, the incidence of medical impoverishment and its depth in the poverty gap remained stable before 2002 and decreased rapidly after 2002. Third, income and regional inequality in measures of catastrophic health expenditure widened from 1986 to 2002. They narrowed in the 2000s but remain wide. Fourth, income and regional inequality in medical impoverishment remained unchanged between 1986 and 2002 and narrowed substantially after 2002. All these results suggest that China's two cycles of health care reform generated significantly different outcomes in financial protection, holding lessons for the ongoing health care reform in China and other countries.